Warranty obligations in Western France, 1040-1270 : law, custom, and lordship - McHaffie, Matthew (Matthew W.) (Palgrave Macmillan, 2023)
This open access book examines warranty obligations in western France during the central Middle Ages. Warranty refers to the commitments that an individual undertook when alienating property to protect the transfer from outside challenge, and to provide compensation if they failed to defend a transaction successfully. The subject has never received a full-length study before, meaning that scholars interpretation of warranty is marred by a number of untested generalisations. Warranty has generally only been viewed as a thirteenth-century development owing to the influence of Roman law and changes in family structure. This book, therefore, considers the evidence for warranty in western France en masse, starting with the first appearance of warranty clauses in documents in the 1040s up until the compilation of vernacular lawbooks in the 1270s. This book opens a window onto legal practice in the central Middle Ages, raising questions about wider processes of legal change. It emphasises the importance of lordship, in particular, when it comes to making sense of how and why warranty obligations developed the way they did. It thus challenges the prevailing explanatory narratives invoked by scholars when discussing warranty, and invites us to ask questions about the sorts of stories we tell when looking at legal change. Combining documentary and prescriptive lawbooks, along with a rich corpus of case material, this book offers a comprehensive account of a little-studied phenomenon, one that can elucidate much larger interpretative questions that are central to French legal history.
Keywords: Real property -- France -- History -- To 1500.; Restraints on alienation -- France -- History -- To 1500.; Real property; Restraints on alienation; France; To 1500; History